Standardized training in the rating of the six-item positive and negative syndrome scale (PANSS-6). (13th April 2021) - Kølbæk, P.; Dines, D.; Hansen, J.; Opler, M.; Correll, C.; Mors, O.; Østergaard, S.
Abstract : Introduction: The six-item Positive And Negative Syndrome Scale (PANSS-6) is short psychometric valid scale quantifying the severity of core schizophrenia symptoms. Using PANSS-6 to guide treatment decision-making requires that staff members' ratings are valid and reliable. Objectives: The objective of the study was to evaluate whether such valid and reliable PANSS-6 ratings can be obtained through a video-based training program. Methods: One-hundred-and-four staff members from Aarhus University Hospital - Psychiatry, Denmark participated in the training. Participants conducted baseline PANSS-6 ratings based on a video of a patient being interviewed using the Simplified Positive And Negative Symptoms interview (SNAPSI). Subsequently, a theoretical introduction video was displayed followed by five SNAPSI patient interviews. After each SNAPSI video, individual ratings were performed before a video providing the gold standard scores was displayed. The validity of ratings was estimated by calculating the proportion of participants not deviating from the gold standard scores with >2 points on individual items or >6 points on the PANSS-6 total score. Reliability was evaluated after each step in the training by means of Gwet's Agreement Coefficient (Gwet). Results: By the end of the training, 72% of the participants rated within the acceptable deviations of the gold standard, ranging from 60% (nurses) to 91% (medical doctors/psychologists). The reliability improved (Gwet baseline vs. endpoint) for all PANSS-6 items, except for Blunted affect. Conclusions: The majority of the staff members conducted valid PANSS-6 ratings after a brief standardized training program, supporting the implementation of PANSS-6 in clinical settings to facilitate measurement-based care. Conflict of interest: Dr. Opler is a full-time employee of MedAvante-ProPhase Inc. Dr. Correll has been a consultant and/or advisor to or have received honoraria from: Acadia, Alkermes, Allergan, Angelini, Axsome, Gedeon Richter, Gerson Lehrman Group, Indivior, IntraCellular T